Efficacy of ultrasound-guided bilateral erector spinae plane block for postoperative analgesia in laparoscopic sleeve gastrectomy. A retrospective cohort study - Karaca, Omer; Polat, Yilmaz (Annals of Medical Research, 2021)
Aim: Laparoscopic sleeve gastrectomy (LSG) causes moderate to severe pain. The present study was planned to evaluate the efficacy and safety of bilateral erector spinae plane block (ESPB) under ultrasound.Material and Methods: A total of 38 patients who underwent LSG between November 2018 and Januvary 2020 were retrospectively analyzed. Patients were divided into two groups: The Control Group (group c, n=19) received only an intravenous (iv) patient controlled analgesia (PCA) and the ESPB Group (group E, n=19) received bilateral ESPB (bupivacaine 0.25, 50 ml) and iv PCA. Results: The numeric rating scores (NRS) at 20th min, 40th min, 1st, 2nd, 4th, 6th, 8th, 12th and 36th hour at the passive period were higher in Group C than in Group E (p0.0001 each). 24th,48th and 72nd hour NRS scores at the passive period were also higher in group C than in group E (respectively, p=0.0001, p:0.0003, p=0.01). 20th min, 40th min, 1st, 2nd, 6th, 8th, 12th, 24th and 36th hour NRS scores at the active period were also higher in Group C than in Group E (p0.0001 each). 4th, 48th and 72nd hour NRS scores at the active period were higher in Group C than in Group E (respectively, p0.0001, p0.0001, p=0.0002). The fentanyl consumption at all the periods were lower in the Group E (p0.0001). PACU and hospital stay durations were shorter in the Group E (p0.0001). Intraoperative fentanyl requirement was lower in the Group E (p=0.003). The first analgesic need time was later in group E (p=0.017). The unassisted walking time was shorter in the Group E (p0.0001). The rescue analgesic requirement was lower in the Group E (p0.0001). The PACU and hospital stays were shorter in group E (p0.0001). No block-related complications and opioid-related side effects were encountered.Conclusion: Pre-incisional bilateral ultrasound guided ESPB provide superior analgesia and shortens unassisted walking time and hospital stay after LSG.